2009
DOI: 10.1002/qsar.200810166
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Studies of HEPT Derivatives Using Support Vector Machines

Abstract: Human Immunodeficiency Virus type 1 reverse transcriptase is an important target for chemotherapeutic agents against the AIDS disease. 1-[2-Hydroxyethoxy-methyl]-6-(phenylthio) thymine] derivatives are potent nonnucleoside reverse transcriptase inhibitors. In the present work, quantitative structure-activity relationship analysis for a set of 79 HEPT derivatives has been investigated by means of support vector machines. The relationships between structure and activity were examined quantitatively using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Another study examined SVM's effectiveness and prognostication power in HEPT derivative QSAR modeling. This investigation showed that SVM outperformed different approaches, including artificial neural networks, in terms of prediction [81]. SVM was also used to simulate phenethylamines' structure-activity relationships (SAR).…”
Section: Support Vector Machinementioning
confidence: 98%
“…Another study examined SVM's effectiveness and prognostication power in HEPT derivative QSAR modeling. This investigation showed that SVM outperformed different approaches, including artificial neural networks, in terms of prediction [81]. SVM was also used to simulate phenethylamines' structure-activity relationships (SAR).…”
Section: Support Vector Machinementioning
confidence: 98%
“…., a n ] T . By combining Equations (7) and (8), the eigenvalue problem can be represented by the following simple form:…”
Section: Kernel Principal Component Analysis (Kpca)mentioning
confidence: 99%
“…At present, many SAR modeling tools have been successfully employed to describe and build this relationship [2][3][4][5][6][7], for example, Artificial Neural Networks (ANN), Decision Tree (DT), Partial Least Squares (PLS), k-Nearest Neighbors (k-NN), Multiple Linear Regression (MLR), Linear Discriminant Analysis (LDA) and Support Vector Machine (SVM). Among all these modeling methods, SVM has been one of the most popular modeling tools in the SAR study due to its prediction performance in terms of accuracy [7][8][9][10][11][12]. However, many researchers have pointed out that SVM also suffered from the problem of feature subset selection [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, inhibitors targeted on protease, integrase and reverse transcriptase (RT) are mainly investigated. [3][4][5][6][7][8][9][10] These compounds have shown great promise in the therapy of HIV infection, particularly in combination therapy because of their high selectivity and their diminished toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…11 Currently there is considerable interest in the set up of QSAR of HIV-1 inhibitors on protease, integrase and RT respectively. [3][4][5] However, these experiments were mainly focused on specific types of targets individually. How to computationally (virtually) screen drug-like inhibitors jointly and simultaneously against multiple protein targets, taking into account protein-inhibitor dynamics with the QSAR modeling is still sparsely interpreted.…”
Section: Introductionmentioning
confidence: 99%